New hemostatic device for grade IV–V liver injury in porcine model: a proof of concept - Juan José Segura-Sampedro; Cristina Pineño-Flores; Andrea Craus-Miguel; Rafael Morales-Soriano; Francesc Xavier González-Argente (World Journal of Emergency Surgery, 2019)
Abstract Background The liver is the most injured organ following abdominal trauma. Uncontrolled bleeding remains the main cause of early liver injury-related death, with a mortality rate of 50–54% in the first 24 h after admission and with 80% of operative deaths. Packing and reoperation account for the increased survival in severe liver trauma, and they are recommended for severe liver injuries (grades IV–V). Perihepatic packing can lead to several potential complications. An excessive packing can cause complications due to abdominal compartment syndrome, while a soft packing may be ineffective, and thus, bleeding can continue inadvertently with the consequent hypovolemic shock and potentially death. Methods We designed a new vacuum-based device to perform perihepatic packing without the negative side-effects of the classic technique. We conducted a prospective pilot feasibility study in a porcine model. We compared the traditional perihepatic packing (PHP) (n = 2) with the new VacBagPack device (VBP) (n = 2). Results Both pigs survived with the new device and showed an equivalent outcome to the one that survived in the traditional technique group. Blood tests were similar too. This suggests that VBP could be at least as effective as traditional PHP. Conclusions We establish a first step towards the development of a new packing device. A new study with a bigger sample size still in pigs will be conducted. Also, an industrial model of the device is currently in production.